Enhancement of the Inhibitor Efficiency of 4-Phenyl-1, 2-dithiol-3-thione on Corrosion of Mild Steel for 20% Sulphuric Acid. - Yousfi, Mohamed; Dakmouche, M; Saidi, M; Hadjadj, M; Rahmani, Z (Asian Journal of Chemistry, 2012)
Subtituted 4-phenyl-1, 2-dithiol-3-thione (PDTT) synthesized and tested as inhibitors for the corrosion for mild steel in the presence of oxygen by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) technique in 20% H2SO4 at 25 ºC. This organic compound inhibits the acidic corrosion even at low concentration. The results obtained show that these sulfur compound is good inhibitors and are in good agreement. Polarization curves indicate that 4-phenyl-1, 2-dithiol-3-thione is a cathodic inhibitor and able to reduce the corrosion current, obtained from electrochemical impedance spectroscopy measurment, were analyzed to model the corrosion inhibition process throught appropriate equivalent circuit model. The adsorption of 4-phenyl-1, 2-dithiol-3-thione on the steel surface in 20% H2SO4 solution, obeys to Langmuir's isotherm with a very hight negative value of the free energy of adsorption∆ Gºad.
Keywords: Acid; Corrosion; Inhibition; Dithiole thione; Mild steel; Electrochemical impedance spectroscopy; Adsorption